Factors influencing student enrolment in young universities: A case study in Zimbabwe - Vitalis Basera; Simbabrashe Munikwa (Goodwood Publishing, 2025)
Purpose: This study explored factors affecting students’ enrolment in young universities, focusing particularly on one young university in Zimbabwe. Young universities are experiencing enrolment challenges, which involve investigating the causal factors for sustainable development and operations of the universities. Research methodology: The study adopted the interpretivist paradigm and used a combination of qualitative approaches for data collection and analysis within a case study design. The study’s sample comprised ten heads of department, one admissions registrar and forty-eight students purposively selected from a young university. In-depth interviews and focus group discussions were used to generate the data. The data were analyzed using a directed content analysis approach. Results: The study revealed that students’ university enrolment is affected mainly by students’ experiences, career orientations, changes in high school graduate preferences, admissions process, transport, accommodation, programmes offered, competition in university education, social capital variables, government policy, cost of education, and disasters. Conclusions: The revealed key stakeholders influencing students’ enrolment in young universities reflected strategies that can be used to increase students’ enrolment, chiefly public awareness, academic support, and student support services. Limitations: While this study adopted a qualitative methodology, which can be a limiting factor in terms of inference, for further research, the study recommends the adoption of a quantitative method. Contribution: This study recommends that universities strategically plan for student enrolment using a multi-stakeholder approach. The study also recommends that the government adequately fund university development and ensure that university education is affordable to everyone.